2021
DOI: 10.1111/ina.12832
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mutagenicity of two common indoor air pollutants, formaldehyde and toluene

Abstract: Traditionally, direct‐reading instruments have been used to directly determine the concentrations of indoor air pollutants that may exceed the regulation limits. However, these instruments cannot directly assess the potential health hazards of these pollutants to humans. In this study, we developed and improved a bacterial reverse mutation assay (Ames test) by using a direct gas exposure module to directly determine the mutagenicity of indoor air quality using five tester bacterial strains (TA98, TA100, TA102,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Toxic and mutagenic effects probably coexisted in the TA100 exposed to IS of 24–36 incense sticks, and the mutagenic effects may balance the toxicity. Our previous study also confirmed that long‐term HCHO or toluene exposure (14 h) could lead to toxic effects on tester TA100 26 . Early studies have reported that HCHO solution displayed toxic effects on specific tester strains, such as TM677 or Escherichia coli , 40,41 thereby partially supporting the above finding.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Toxic and mutagenic effects probably coexisted in the TA100 exposed to IS of 24–36 incense sticks, and the mutagenic effects may balance the toxicity. Our previous study also confirmed that long‐term HCHO or toluene exposure (14 h) could lead to toxic effects on tester TA100 26 . Early studies have reported that HCHO solution displayed toxic effects on specific tester strains, such as TM677 or Escherichia coli , 40,41 thereby partially supporting the above finding.…”
Section: Resultssupporting
confidence: 85%
“…Thus, we speculate that the long-term exposure of this IS to TA100 may also contribute to toxic effects, as demonstrated from the toxic effect of HCHO exposure to TA00 in our previous report. 26 Furthermore, a dose-response effect was observed when the tester strain was exposed to IS of 6 and 12 incense sticks for 10 min in the presence of metabolic activation (Table 6), which was consistent with the IS of 3 and 6 incense sticks for 30 and 60 min, respectively. Additionally, a weak but significant time-response effect was observed when the tester strain was exposed to IS of 3 and 6 incense sticks at 10- relatively stronger mutagenic activities than that of brand A.…”
Section: Mutagenic Effects Of Is Of the Two Brandssupporting
confidence: 68%
See 3 more Smart Citations